Pengaruh Kebiasaan Belajar dan Perhatian Orang Tua terhadap Motivasi Belajar Siswa Kelas VIII di SMP Negeri 2 Kubung - Khairi, Ummul; Ilyas, M. (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2023)
This study aims to examine: 1) The effect of study habits on students' learning motivationof eighth grade students at SMP Negeri 2 Kubung. 2) The effect of parental attention on students' learning motivation of eighth grade students at SMP Negeri 2 Kubung. 3) The influence of study habits through parental attention to the learning motivation of class VIII students at SMP Negeri 2 Kubung.4) The influence of study habits and parental attention simultaneously on the learning motivation of eighth grade students at SMP Negeri 2 Kubung. The analysis technique used is path analysis. The results of this study indicate that: 1) There is a positive and partially significant effect between study habits on students' learning motivation, where > is 9.263 > 1.668. 2) There is a positive, partially significant effect between parents' attention to students' learning motivation, where > is 3.155 > 1.668. 3) There is a positive and significant influence between study habits through parental attention to students' learning motivation, which is obtained > which is 3.40 > 1.668.4) There is a simultaneous positive and significant effect between study habits and parental attention on students' learning motivation, where > is 61.557 > 3.11 with a significant level = 5%.